Bariogénesis a través de leptogénesis (2009)
By adding right-handed Majorana neutrinos to the standard model, their out of equilibrium decays, which violate lepton number, combined with anomalous electroweak processes, can generate the baryon asymmetry of the Universe. We briey review this model, including the cross-sections which enter Boltzmann equations, and find approximate solutions to them. We also establish plausible ranks for the parameters to obtain an asymmetry of the same order of the one observed, YB~10-11.